Analysis of the effect of anti-tuberculosis therapy combined with all-in-one nursing care on the alleviation of inflammation in patients with pulmonary tuberculosis: Improvement of tuberculosis by all-in-one nursing care - Liu, Anqi; Yin, Xiaohong; Wang, Rui; Cheng, Liang; Zhang, Yingying; Tu, Fan; Ma, Jun; Zhong, Yutao (Cellular and Molecular Biology, 2023)
To analyze the application effect of anti-tuberculosis therapy (ATT) combined with all-in-one nursing care on pulmonary tuberculosis (PT). Seventy-four PT patients who received ATT in our hospital between December 2015 and June 2016 were selected as the research participants and randomized into a research group (RG; n=37) and a control group (CG; n=37) that were given all-in-one nursing care and routine care, respectively. The cure rate and treatment compliance were compared between groups, and the awareness of disease prevention and treatment was investigated. Patients’ psychological status and quality of life were evaluated using the Self-Rating Depression/Anxiety Scale (SAS/SDS) and the Quality of Life Questionnaire Core 30 (QLQ-C30), respectively. RG and CG were not statistically different in the clinical cure rate (P>0.05), but the X-ray cure rate was higher and the recurrence rate was lower in RG (P<0.05). In addition, RG showed higher medication compliance rate, regular reexamination rate and awareness of disease prevention and treatment than CG (P<0.05). Reductions in SAS/SDS scores were observed in both groups after care, with even lower levels in RG, while the QLQ-C30 score increased and was higher in RG as compared to CG (P<0.05). Therefore, All-in-one nursing care can effectively enhance the level of treatment compliance and awareness of disease prevention and treatment of PT patients. In the future, when treating PT patients in the clinic, the effectiveness of ATT can be improved by implementing all-in-one nursing care to provide more reliable prognosis for patients.